2023
DOI: 10.1302/0301-620x.105b10.bjj-2023-0115.r1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E-diffused liners show less head penetration than cross-linked polyethylene liners in total hip arthroplasty: a ten-year multi-arm randomized trial

Joseph A. N. El-Sahoury,
Kristian Kjærgaard,
Ole Ovesen
et al.

Abstract: AimsThe primary outcome was investigating differences in wear, as measured by femoral head penetration, between cross-linked vitamin E-diffused polyethylene (vE-PE) and cross-linked polyethylene (XLPE) acetabular component liners and between 32 and 36 mm head sizes at the ten-year follow-up. Secondary outcomes included acetabular component migration and patient-reported outcome measures (PROMs) such as the EuroQol five-dimension questionnaire, 36-Item Short-Form Health Survey, Harris Hip Score, and University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a ten-year multi-arm randomized trial, investigators from Odense (Denmark) reported on the performance of vitamin E-diffused polyethylene (vE-PE) hip liners as compared to standard cross-linked polyethylene (XLPE) liners in total hip arthroplasty (THA). 6 The study aimed to assess differences in femoral head penetration between these two types of liners and in the context of femoral head sizes of 32 mm and 36 mm. The trial was designed as a single-blinded, 2 × 2 factorial randomized controlled trial.…”
Section: Vitamin E – a Positive Thing In Your Poly?mentioning
confidence: 99%
“…In a ten-year multi-arm randomized trial, investigators from Odense (Denmark) reported on the performance of vitamin E-diffused polyethylene (vE-PE) hip liners as compared to standard cross-linked polyethylene (XLPE) liners in total hip arthroplasty (THA). 6 The study aimed to assess differences in femoral head penetration between these two types of liners and in the context of femoral head sizes of 32 mm and 36 mm. The trial was designed as a single-blinded, 2 × 2 factorial randomized controlled trial.…”
Section: Vitamin E – a Positive Thing In Your Poly?mentioning
confidence: 99%